An Outcome Based Exploration of Pharmacotherapeutics in Chronic Mechanical Non-Specific Low Back Pain (CNLSBP) Patients in Tertiary Care Hospital - Shantanu Basu Mullick; Debasree Debbarma; Anirban Sadhu; Arijit Ghosh (International Journal of Health and Clinical Research, 2021)
Background: Low back pain is a symptomatic condition with multifactorial causation. It is characterized by pain & muscle stiffness or tension. The aim of management of low back pain is to relieve the pain quickly, to improve functional ability & prevention of disability. A range of Non-Steroidal Anti-Inflammatory drugs (NSAIDs) are used for management which provides variable symptomatic relief.Aims and objectives: To evaluate the pattern and prescribing trends of therapy with different NSAIDS & to evaluate the efficacy of different pharmacotherapeutics in the management of chronic mechanical nonspecific low back pain by using visual analogue scale (VAS) score and Oswestry Disability Index (ODI) score.Materials and methods: This prospective, observational, and questionnaire-based study was conducted in the Department of Physical Medicine and Rehabilitation center (PMR) of RG Kar Medical College and Hospital, Kolkata. 130 newly diagnosed CNSLBP patients were selected after satisfying inclusion and exclusion criteria. NSAIDs involved in the study are Aceclofenac, Paracetamol, Ibuprofen, Etodolac, Etoricoxib, Naproxen, Piroxicam. Mean VAS score and ODI score were evaluated in all patients at 0, 4, 8 and 12 weeks to assess the efficacy of NSAIDs in reducing pain and functional disability. Results: Among 130 patients involved in the study, 84(65%) were female and 46(35%) were male patients and the mean age of female was 40.46 and that of male was 39.96 years. All the different NSAIDS involved in this study were effective in reducing pain and functional disability in CNSLBP patients as evaluated by VAS score and ODI score.